2023
DOI: 10.1111/plb.13551
|View full text |Cite
|
Sign up to set email alerts
|

Seed coat composition in black and white soybean seeds with differential water permeability

Abstract: The seed coat composition of white (JS 335) and black (Bhatt) soybean (Glycine max (L.) Merr) having different water permeability was studied. Phenols, tannins and proteins were measured, as well as trace elements and metabolites in the seed coats. The seed coat of Bhatt was impermeable and imposed dormancy, while that of JS 335 was permeable and seeds exhibited imbibitional injury. Bhatt seed coats contained comparatively higher concentrations of phenols, tannins, proteins, Fe and Cu than those of JS 335. Met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
(75 reference statements)
0
0
0
Order By: Relevance
“…Three major phenolics, namely epicatechin, cyanidin-3-O-glucoside, and delphinidin-3-O-glucoside, were isolated from wild soybean seed coats, and the changes in epicatechin content were significantly positively correlated with the HS trait under different water conditions during seed development and under different gas conditions during seed storage (Zhou et al, 2010). Similarly, Vijayan et al (2023) measured the phenols, tannins, proteins, trace elements, and metabolites in the seed coats of two soybean cultivars exhibiting different levels of water permeability. They found that phenols are the main compounds responsible for seed coat impermeability, which may provide strength to the seed coat.…”
Section: Internal and External Factors Affecting The Hs Traitmentioning
confidence: 99%
“…Three major phenolics, namely epicatechin, cyanidin-3-O-glucoside, and delphinidin-3-O-glucoside, were isolated from wild soybean seed coats, and the changes in epicatechin content were significantly positively correlated with the HS trait under different water conditions during seed development and under different gas conditions during seed storage (Zhou et al, 2010). Similarly, Vijayan et al (2023) measured the phenols, tannins, proteins, trace elements, and metabolites in the seed coats of two soybean cultivars exhibiting different levels of water permeability. They found that phenols are the main compounds responsible for seed coat impermeability, which may provide strength to the seed coat.…”
Section: Internal and External Factors Affecting The Hs Traitmentioning
confidence: 99%